Convergent evolution of pregnancy-specific glycoproteins in human and horse. Issue 3 (September 2016) - Aleksic, Denis; Blaschke, Lisa; Mißbach, Sophie; Hänske, Jana; Weiß, Wiebke; Handler, Johannes; Zimmermann, Wolfgang; Cabrera-Sharp, Victoria; Read, Jordan E; de Mestre, Amanda M; O'Riordan, Ronan; Moore, Tom; et al.
Abstract : Pregnancy-specific glycoproteins (PSGs) are members of the carcinoembryonic antigen cell adhesion molecule (CEACAM) family that are secreted by trophoblast cells. PSGs may modulate immune, angiogenic and platelet responses during pregnancy. Until now, PSGs are only found in species that have a highly invasive (hemochorial) placentation including humans, mice and rats. Surprisingly, analyzing the CEACAM gene family of the horse, which has a non-invasive epitheliochorial placenta, with the exception of the transient endometrial cups, we identified equine CEACAM family members that seem to be related to PSGs of rodents and primates. We identified seven genes that encode secreted PSG-like CEACAMs . Phylogenetic analyses indicate that they evolved independently from an equine CEACAM1 -like ancestor rather than from a common PSG -like ancestor with rodents and primates. Significantly, expression of PSG-like genes ( CEACAM44, CEACAM48, CEACAM49 and CEACAM55 ) was found in non-invasive as well as invasive trophoblast cells such as purified chorionic girdle cells and endometrial cup cells. Chorionic girdle cells are highly invasive trophoblast cells that invade the endometrium of the mare where they form endometrial cups and are in close contact with maternal immune cells. Therefore, the microenvironment of invasive equine trophoblast cells has striking similarities to the microenvironment of trophoblast cells in hemochorial placentas, suggesting that equine PSG-like CEACAMs and rodent and primate PSGs have undergone convergent evolution. This is supported by our finding that equine PSG-like CEACAM49 exhibits similar activity to certain rodent and human PSGs in a functional assay of platelet–fibrinogen binding. Our results have implications for understanding the evolution of PSGs and their functions in maternal–fetal interactions.